2001
DOI: 10.1074/jbc.m104036200
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Regulates the Level and Stability of Cyclooxygenase-2 mRNA through Activation of p38 Mitogen-activated Protein Kinase in Interleukin-1β-treated Human Synovial Fibroblasts

Abstract: The p38 MAPK mediates transcriptional and posttranscriptional control of cyclooxygenase-2 (COX-2) mRNA following interleukin-1(IL-1)/lipopolysaccharide cellular activation. We explored a positive feedback, prostaglandin E 2 (PGE 2 )-dependent stabilization of COX-2 mRNA mediated by the p38 MAPK cascade in IL-1␤-stimulated human synovial fibroblasts. We observed a rapid (5 min), massive (>30-fold), and sustained (>48 h) increase in COX-2 mRNA, protein, and PGE 2 release following a recombinant human (rh) IL-1␤ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
146
2
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 186 publications
(157 citation statements)
references
References 61 publications
(98 reference statements)
8
146
2
1
Order By: Relevance
“…Kinase p38 can phosphorylate members of the CREB/ATF family, rendering them transcriptionally competent (51). It has recently been demonstrated that p38 MAP kinase and the cAMP/PKA pathway interact to transactivate the cox-2 promoter in response to IL-1␤ in human synoviocytes (32). We have confirmed that CRH signals through similar CREB/ATF factors in RA synovium and rapidly contributes to enhanced CREB-1 and ATF-2 binding activity in primary RA endothelial cells.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Kinase p38 can phosphorylate members of the CREB/ATF family, rendering them transcriptionally competent (51). It has recently been demonstrated that p38 MAP kinase and the cAMP/PKA pathway interact to transactivate the cox-2 promoter in response to IL-1␤ in human synoviocytes (32). We have confirmed that CRH signals through similar CREB/ATF factors in RA synovium and rapidly contributes to enhanced CREB-1 and ATF-2 binding activity in primary RA endothelial cells.…”
Section: Discussionsupporting
confidence: 70%
“…We have confirmed that CRH signals through similar CREB/ATF factors in RA synovium and rapidly contributes to enhanced CREB-1 and ATF-2 binding activity in primary RA endothelial cells. Thus, the findings from these experiments, taken together with those from previous studies (32,51), suggest that COX-2-dependent PGE 2 production by CRH may be due, in part, to the transcriptional activation of CREB/ATF proteins by CRH.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…the EP 2 receptor is induced by inflammatory stimuli. Interestingly, PGE 2 leads to the stabilization of COX-2 mRNA via the EP 4 receptor (interaction with the p38 MAPK pathway) (Faour et al, 2001).…”
Section: -10mentioning
confidence: 99%